Towards a Global History of Horse Racing. Issue 3 (3rd March 2020) - Bell, Sinclair; Jaser, Christian; Mann, Christian
Abstract: By investigating the global history of horse racing from antiquity to the modern period, it is likewise possible to overcome the traditional pitfalls in the periodization of sport history. Instead of claiming an exclusiveness of modern sport and downgrading premodern physical contests as pure phenomena of alterity, this special issue discusses racing in the horse age as a deep history of diachronically comparable practices, discourses, and perceptions centered around the competitive staging of equine speed.